2018
DOI: 10.1080/1478601x.2018.1492919
|View full text |Cite
|
Sign up to set email alerts
|

To protect and collect: a nationwide study of profit-motivated police crime

Abstract: This study is part of a larger research project on police crime in the United States. Police crimes are those criminal offenses committed by sworn law enforcement officers who have the general powers of arrest. Profit-motivated police crime involves officers who use their authority of position to engage in crime for personal gain. This study reports the findings on 1,591 cases where a law enforcement officer was arrested for one or more profit-motivated crimes during the seven-year period 2005-2011. The profit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
(29 reference statements)
2
11
1
Order By: Relevance
“…Interestingly, the current study concluded that agency-level factors (i.e., type of agency, number of sworn officers) played a significant role in female officers' unlawful behavior, which paralleled Stinson, Liederbach, et al's studies (Stinson, Liederbach, et al, 2015;Stinson, Liederbach, Brewer, & Todak, 2013;Stinson, Liederbach, Brewer, Schmalzried, et al, 2013;Stinson et al, 2018) that found that departmental-level attributes shaped officers' behavior and performance across states. The results also indirectly echoed the "rotten barrels" thesis (Gottschalk, 2012b(Gottschalk, , 2012c for which contextual features are influential over female officers' misconduct and certain macro-level attributes encourage corrupt behavior.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Interestingly, the current study concluded that agency-level factors (i.e., type of agency, number of sworn officers) played a significant role in female officers' unlawful behavior, which paralleled Stinson, Liederbach, et al's studies (Stinson, Liederbach, et al, 2015;Stinson, Liederbach, Brewer, & Todak, 2013;Stinson, Liederbach, Brewer, Schmalzried, et al, 2013;Stinson et al, 2018) that found that departmental-level attributes shaped officers' behavior and performance across states. The results also indirectly echoed the "rotten barrels" thesis (Gottschalk, 2012b(Gottschalk, , 2012c for which contextual features are influential over female officers' misconduct and certain macro-level attributes encourage corrupt behavior.…”
Section: Discussionsupporting
confidence: 75%
“…A corrupt police organization breeds the corrupt culture, values, and procedures that influence police officers' behavior and decision-making in everyday policing. Prior studies report that agency-level attributes such as agency type (Stinson et al, 2012;Stinson, Liederbah et al, 2015;Stinson et al, 2018;Stinson, Todak et al, 2015), region (Stinson et al, 2012;Stinson, Liederbach, Brewer, Schmalzried et al, 2013;Stinson et al, 2018), numbers of officers (Stinson, Liederbach, Brewer, & Todak et al, 2013;Stinson et al, 2018), rurality (Stinson, Liederbach et al, 2018), and jurisdiction (Donner, Fridell et al, 2016) affected police crime and misconduct. Carter (1990) reported that environmental factors and the structure of law enforcement would shape officers' behavior particularly if officers were working directly in areas where drug issues are common and drug crime is prevalent.…”
Section: Individual and Contextual Attributes Of Police Crimementioning
confidence: 99%
See 1 more Smart Citation
“…Decision tree techniques are beneficial due to their ability to handle interaction effects in data without being bound to statistical assumptions (Sonquist 1970). Classification tree analysis has been used to examine police practices including careerending police misconduct (Kane and White 2013), police drug corruption arrests , fatal and nonfatal incidents involving conductive energy devices (White and Ready 2009), police sexual misconduct (Stinson et al 2014a(Stinson et al , 2014c, and profit-motivated police crime (Stinson et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Research focused on the arrest of police officers involved in drug-related corruption and crime identified drug trafficking and sales as the most recurrent pattern, but the secondmost prevalent pattern of criminal behavior involved thefts/shakedowns of street-level drug dealers by police . A study on the profit-motivated crimes of police found this phenomenon most commonly involved some form of nonviolent theft from persons, buildings, and also embezzlement (Stinson et al 2018).…”
Section: Research On Police Crime and Victimizationmentioning
confidence: 99%